Voluntary control of arm movement in athetotic patients - Neilson, Peter D. (1974)
Visual tracking tests have been employed to provide a quantitative description of voluntary control of arm movement in a group of patients suffering from athetoid cerebral palsy. Voluntary control was impaired in all patients in a characteristic manner. Maximum velocity and acceleration of arm movement were reduced to about 30-50% of their values in normal subjects and the time lag of the response to a visual stimulus was two or three times greater than in normals. Tracking transmission characteristics indicated a degree of underdamping which was not presnet in normal or spastic patients. This underdamping could be responsible for a low frequency (0·3-0·6 Hz) transient oscillation in elbow-angle movements associated with sudden voluntary movement. The maximum frequency at which patients could produce a coherent tracking response was only 50% of that in normal subjects and the relationship between the electromyogram and muscle contraction indicated that the mechanical load on the biceps muscle was abnormal, possibly due to increased stiffness of joint movement caused by involuntary activity in agonist and antagonist muscles acting across the joint.